1991
DOI: 10.3109/07853899109148082
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Helicobacter and Upper Gastrointestinal Symptoms in Chronic Renal Failure

Abstract: We studied histologically antral biopsies from 89 consecutive patients with chronic renal failure for Helicobacter pylori (previously Campylobacter pylori). A dose-response gastric secretion test was also performed. The frequency of Helicobacter-positive subjects was low (15/89, 17%), corresponding to figures reported in the literature for young symptomless volunteers. Helicobacter-positive patients had significantly more frequently upper gastrointestinal symptoms than Helicobacter-negative individuals (P less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…,22 Most dialysis patients suffer from upper gastrointestinal symptoms 8,23. Similar results were found in our study, and almost all patients with ESRD undergoing PD experienced gastrointestinal discomfort.…”
supporting
confidence: 87%
“…,22 Most dialysis patients suffer from upper gastrointestinal symptoms 8,23. Similar results were found in our study, and almost all patients with ESRD undergoing PD experienced gastrointestinal discomfort.…”
supporting
confidence: 87%
“…Offerhause et al [16] reported that H. pylori plays no role in ulcer dia thesis, while Ala-Kaila et al [17] reported significantly more frequent upper gastrointestinal symptoms and an tral gastritis in H. pylori-positive patients.…”
Section: Resultsmentioning
confidence: 99%
“…pylori due to the high gas tric urea and the immunosuppressive state. Several recent reports demonstrated a lower detection rate of H. pylori in uremics than normal controls [16][17][18], This may be a true finding which could be explained by frequent use of drugs including antibiotics by uremic patients or this could be due to false-negative testing, e.g. detection of antibody or urease test.…”
Section: Resultsmentioning
confidence: 99%
“…Ala-Kaila et al showed that pentagastrin-stimulated gastric acid secretion is greater in //. pylori-positive patients with chronic renal failure than in their H. pylori-ncg^tive counterparts (6). In addition to augmentation of the gastric acid secretion, H. pylori may cause mucosal injury due to the increased production ofgastricjuice ammonia (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the influence of H. pylori infection on the serum gastrin concentration in patients with end-stage renal disease have been limited and the results are conflicting. Luzza et al reported thatpatients on dialysis with H. pylori infection exhibit a higher serum gastrin concentration than those without H. pylori infection (5), while other studies have not found such differences (6)(7)(8).…”
Section: Introductionmentioning
confidence: 98%